Synopsis of the shore bugs of China (Hemiptera: Heteroptera: Leptopodomorpha: Saldidae) - Vinokurov, Nikolai N.; Cai, Wanzhi; Chen, Ping-Ping (Zootaxa, 2018)
In China, most research on shore bugs (Hemiptera: Leptopodomorpha: Saldidae) has been conducted intermittently during the second half of the 19th century. Records from the literature supplemented by our collections were used to construct an annotated list of 50 species in 13 genera and 2 subfamilies (Chiloxanthinae and Saldinae) of Saldidae now known from China. This paper also presents new distributional records and color plates depicting 26 species. Further, a list of 12 species of Saldidae known in neighboring territories that might occur in China is presented.